The Review of Science Education in China - Zhang, Hui (Technium Social Sciences Journal, 2021)
Science education is paid more attention nowadays. This article describes the current situation of Science education in China. As a concept paper, it is divided into some aspects, such as the history and development, the Necessity of Science history, incorporate the history of science into today’s science education, the future trend of science education, the goal and significance of science education, also, it states the problems and solutions in science education as well. More importantly, science education in the 21st Century is introduced in the end which combines the advanced technology in science teaching and learning process. Conclusion comes lastly with the enlightenment for future development of science education.